Genetic Diversity of Large Japanese Field Mouse Apodemus speciosus Populations and Identification of their Food Plant Resources using DNA Barcoding in an Industrial Green Space - Fujii Taichi; Kawamoto Hirokazu; Shirako Tomoyasu; Ueno Kaoru; Minami Motoyasu (Journal of Plant and Animal Ecology, 2018)
Estimates of the genetic diversity of Large Japanese field mouse Apodemusspeciosus populations and identification of their plant food resources were conducted in an industrial green space, where were constructed on reclaimed land and belonged to the Aichi Refinery of Idemitsu Kosan Co., Ltd., in Aichi Prefecture, Japan. A total of six mitochondrial D-loop haplotypes were identified in 50 mice. Habitat condition with the highest number of captured individuals had abundant broad-leaved trees and understory vegetation. A minimum spanning network, which did not form a ring-shaped network, revealed that the hereditary population structure was weak. The low genetic diversity observed in the study area was thus attributed to isolation from other populations once the population in the study area by sea and road, which is more than 30 m wide. In order to identify which plant food resources were utilized by mice captured inside the industrial green space, partial chloroplast rbcL sequences were amplified by PCR from DNA extracted from 43 feces samples. Calculations of sample completeness curve revealed that 25 of the taxa identified in this study comprised approximately 90% of the food plant resources in the study area. Of the 21 plant families identified from the obtained rbcL sequences, members of the Rosaceae (28.0%), Fagaceae (17.2%), Lauraceae (14.2%) and Oleaceae (7.7%) were dominant. To ensure the continued survival of A. speciosuspopulation in this industrial green space would be to preferentially conserve plant species that are used as food resources by this species.
Keywords: Apodemusspeciosus